Periodic solutions of vdP and vdP-like systems on 3-Tori - Balanov, Zalman; Hooton, Edward; Murza, Adrian (Topological Methods in Nonlinear Analysis, 2017)
Van der Pol equation (in short, vdP) as well as many its non-symmetric generalizations (the so-called van der Pol-like oscillators (in short, vdPl)) serve as nodes in coupled networks modeling real-life phenomena. Symmetric properties of periodic regimes of networks of vdP/vdPl depend on symmetries of coupling. In this paper, we consider N^3 identical vdP/vdPl oscillators arranged in a cubical lattice, where opposite faces are identified in the same way as for a 3-torus. Depending on which nodes impact the dynamics of a given node, we distinguish between D_N × D_N × D_N-equivariant systems and their Z_N × Z_N × Z_N-equivariant counterparts. In both settings, the local equivariant Hopf bifurcation together with the global existence of periodic solutions with prescribed period and symmetry, are studied. The methods used in the paper are based on the results rooted in both equivariant degree theory and (equivariant) singularity theory.